2018
DOI: 10.2147/ndt.s148921
|View full text |Cite
|
Sign up to set email alerts
|

ADHD and lifestyle habits in Czech adults, a national sample

Abstract: BackgroundAdult attention-deficit/hyperactivity disorder (ADHD) has been added as a diagnosis to the Diagnostic and Statistical Manual of Mental Disorders version 5 (DSM5) in 2013, thus making ADHD, which has been classically known as a childhood disorder, a life-long disorder. Those suffering from the condition show very specific behavioral traits, which manifest as lifestyle habits; they also show comorbidities that can be the symptoms and/or consequences of certain lifestyles.Materials and methodsThe target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 33 publications
1
18
1
Order By: Relevance
“…At the phenotypic level, our results are in line with previous study from adults associating elevated levels of self‐reported ADHD symptoms with higher consumption of sweet food and lower consumption of vegetables and fruits (Weissenberger et al, 2018). However, the case–control study with 51 young adults (aged 18–25) suggested that nutrient intake was not associated with ADHD, but the conclusion was limited by the small sample size leading to low statistical power (Holton et al, 2019).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…At the phenotypic level, our results are in line with previous study from adults associating elevated levels of self‐reported ADHD symptoms with higher consumption of sweet food and lower consumption of vegetables and fruits (Weissenberger et al, 2018). However, the case–control study with 51 young adults (aged 18–25) suggested that nutrient intake was not associated with ADHD, but the conclusion was limited by the small sample size leading to low statistical power (Holton et al, 2019).…”
Section: Discussionsupporting
confidence: 92%
“…However, only two available studies with adult samples were found with conflicting results. Weissenberger et al (2018) reported an association between ADHD symptoms and higher consumption of sweets, while Holton, Johnstone, Brandley, and Nigg (2019) found nutrient intake was not associated with diagnosed ADHD.…”
Section: Introductionmentioning
confidence: 99%
“…Many adults with ADHD symptoms in the Czechia may never be diagnosed with the condition and may suffer because of this bias. This was one of the main reasons for our previous study on the widespread of ADHD symptoms in Czech adults and their associated lifestyles in 2018; please see Weissenberger et al (2018) for more on that. Other studies have looked at ADHD symptoms, time perspectives, along with other issues such as addictive behaviors.…”
Section: Discussionmentioning
confidence: 96%
“…They noted consistencies in time deficits in those with a confirmed diagnosis of ADHD rather than individuals suffering from some of the symptoms but at a low level, whom the authors referred to as ‘pseudo-ADHD’ [44]. In previously reported studies by these authors, the findings showed that adults with strong symptoms of ADHD had unique lifestyles and habits that might make diagnosis and treatment planning easier, and the perception of time could be viewed in similar terms as far as asking the right questions for diagnosis and including time treatments [45]. The inner clock of people with ADHD seems to run faster than in normal individuals, and this can be useful in diagnostics and can be integrated into treatment.…”
Section: Discussionmentioning
confidence: 99%